Pengaruh Kepercayaan dan Kepuasan Kerja terhadap Intensi Turnover Guru SMKS Cikarang Utara - Reinelda Rani Rosalina; Matin Matin; Kamaludin Kamaludin (Universitas Indraprasta PGRI Jakarta, 2018)
This study aims to know the effect of (1) trust, (2) job satisfaction, (3) turnover intention of teachers teaching at private Vocational High School (SMK) in North Cikarang District. Survey method with a quantitative-causal approach using path analyses is used to in this research. The survey was conducted from September to December 2017, involving 125 teachers in a District as randomly determined samples. The findings of this study show: first, there is a directly negative effect of trust on turnover intention. Second, there is a directly negative effect of job satisfaction on turn over intention. Third, there is a directly positive effect of trust on job satisfation. Based on the findings, it is suggested that the Principal whose position is also as a manager in the school be a good role model for the teachers in respecting and appreciating others.